Star rating factors for umrah services: the perspectives of umrah operators and consumers - Harun, Amran; Muslim, Aini Khalida; Dzail, Dzunnur; Othman, Bestoon Abdulmaged (Technological University Dublin, 2020)
The star rating system is widely used in the hotel industry to classify hotels according to their quality. However, the Umrah industry in Malaysia has yet to adopt the system. Thus, their services are not monitored by a controlled and reliable rating system. The star rating is deemed important to Umrah consumers as the system would provide the consumers with information about basic facilities or services that can be expected. Hence, the purpose of this study is to explore the key elements of a star rating that would suit the Umrah industry in Malaysia and to accomplish this, perspectives of Umrah operators and Umrah consumers are gauged. One hundred and eighty-one Umrah operators, namely the marketing managers, were involved in this study as respondents. Three hundred eighty-four individuals who had performed Umrah were also engaged as respondents. The information was then analysed using the Statistical Package for the Social Sciences (SPSS) software. The findings of this study confirmed that the top fivestar rating factors identified by the Umrah operators and Umrah consumers were the mutawwif’s expertise, the hotel, problem-solving, valence, and airlines.